Genotipagem de HLA de classe I e II para seleção de células precursoras dendríticas para estudo da imunobiologia do vírus associado ao Sarcoma de Kaposi (KSHV) - Laszkiewicz, Nathalia Suiti [UNESP] (2011)
The Kaposi-associated Herpesvirus (KSHV) also known as Human Herpesvirus 8 (HHV-8) is associated with the development of Kaposi’s sarcoma (KS) and others limphoprolipheratives diseases such as Primary Effusion Lymphoma (PEL) and Multicentric Castleman Disease (MCD). Even though the virus is considered lymphotropic, it is able to infect others cell types such as macrophages, dendritic cells, endothelial cells, monocytes and fibroblasts. After infection, KSHV be latent expressing essential viral genes to its maintenance in a infected cell. However, in some circumstances may occur the reactivation of lytic cycle producing new viral particles. K1 protein of KSHV interferes in the cellular signaling inducing proliferation and supporting cellular transformation. K1 is encoded by viral ORF-K1, which shows high variability between different genotypes of KSHV. So far, it is not clear whether different isoforms of K1 have specific immunobiological features. The KSHV latency is maintained under strict control by the immune system supported by an adequate antigen presentation involving Human Leucocyte Antigen (HLA) class I and II. Polymorphisms of HLA class I and II genes confer an enormous variability in molecules that recognize a large amount of antigens, but also can increase the susceptibility to autoimmune diseases. Therefore, the present study aims to genotype HLA class I (A and B) and class II (DR and DQ) from volunteers to identify haplotypes that can provide better response to K1 epitopes of different KSHV genotypes. First of all, 20 volunteers were selected to genotype HLA genes. In our results we observed prevalence of certain HLA class I haplotypes as HLAA1, HLA-A2, HLA-A24, HLA-A26, HLA-B8, HLA-B18 e HLA-B44. After the in silico analysis using BIMAS and SYFPEITHI databases, we observed high scores for epitopes from the B genotype of KSHV, indicating...(Complete abstract click electronic access below)